"Arbitrzy i nie tylko...". Duchowni na kartach księgi ławniczej miasta Płocka w latach 1489-1517 - Graczyk, Waldemar (Saeculum Christianum. Pismo Historyczne, 2018)
There are nineteen clerics on the pages of the Plock’s book of assessors in the years 1489-1517. There were primarily associated with the local church environment. Their involvement as arbiters in conflicts is evident; they are also present as the executors of the testaments or the addressee of testament legate, the contractors of acts of buy-sell, the holders of deposits or prudent guardians looking after goods of the Church. The inscription in the Plock’s book of assessors in which we see the clergy, lead to the conclusion that the local representatives of the Church enjoyed trust and authority among the local people.